Meta-analysis of the Effectiveness of Technology Based Entrepreneurship Education in the Digital Era - Yuliandi, Andri; Yulastri, Asmar; Maksum, Hasan; Yuliana, Yuliana; Purwanto, Wawan; Santosa, Tomi Apra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to meta-analyze the effectiveness of technology-based entrepreneurship education in the digital era. Rapid technological developments have driven transformation in entrepreneurial learning methods and approaches, especially through the use of digital platforms, learning applications, and interactive media. The study used a meta-analysis method of 10 relevant scientific articles published between 2013 and 2024. The results of the analysis show that technology-based entrepreneurship education has a significant positive influence on improving students' entrepreneurial competence, creativity, and business readiness with a value of d = 1,015; p < 0.001 high effect size category. These findings affirm the importance of integrating technology in the entrepreneurship curriculum to create adaptive, innovative, and contextual learning. The implication of this research is the need to develop a more systematic and practice-oriented technology-based curriculum and teaching strategies.